Sustainability of the interventions in coconut based homesteads of Central Kerala - Helen, S.; Ahamed, P. (Journal of Plantation Crops, 2011)
An ICAR adhoc scheme on ’Possible Diversifications and Restructuring of Coconut based Homesteads’ was implemented in the six agro-ecosystems of Central zone of Kerala covering three districts namely Palakkad, Thrissur and Ernakulam with the holistic approach in coconut based homesteads from 2005 to 2008 by the participation of all the stakeholders. A comparative index namely Sustainability Development Index was developed for the study, which contained specific indices for economic, social, ecological sustainability, productivity, stability and equity dimensions. After three years of interventions, Sustainability Development Index was found to be the highest at High Elevation- Medium Rainfall (HEMR) situation (Kizhakkenchery) with 41.92. Economic sustainability (56.40) was the highest among all the dimensions because of the visibility of enhanced economic returns and increased employment opportunities. Ecological sustainability and stability were the two dimensions which contributed less for the Sustainability Development Index of the selected homesteads. It was concluded that the interventions on diversifications of coconut based homesteads indicated sustainability.